The Molecular Mechanism of Iron(III) Oxide Nucleation - Scheck, J.; Wu, B.; Drechsler, M.; Rosenberg, R.; Van Driessche, A.; Stawski, T.; Gebauer, Denis (American Chemical Society, 2016)
© 2016 American Chemical Society.A molecular understanding of the formation of solid phases from solution would be beneficial for various scientific fields. However, nucleation pathways are still not fully understood, whereby the case of iron (oxyhydr)oxides poses a prime example. We show that in the prenucleation regime, thermodynamically stable solute species up to a few nanometers in size are observed, which meet the definition of prenucleation clusters. Nucleation then is not governed by a critical size, but rather by the dynamics of the clusters that are forming at the distinct nucleation stages, based on the chemistry of the linkages within the clusters. This resolves a longstanding debate in the field of iron oxide nucleation, and the results may generally apply to oxides forming via hydrolysis and condensation. The (molecular) understanding of the chemical basis of phase separation is paramount for, e.g., tailoring size, shape and structure of novel nanocrystalline materials.